Prenatal stress induces transient developmental alterations in distinct GABAergic populations and leads to long-lasting behavioral abnormalities - Keren Shoshani-Haye; Gilgi Friedlander; Ofra Golani; Suellen Almeida-Correa; Yair Shemesh; Alon Chen (Neurobiology of Stress)
Prenatal stress (PNS) is a well-established risk factor for psychiatric disorders, yet the underlying neurobiological mechanisms remain unclear. Here, we demonstrate that PNS induces long-term behavioral abnormalities, including increased anxiety- and depressive-like behaviors specifically in adult male mice. To investigate potential neurodevelopmental disruptions, we analyzed the medial prefrontal cortex (mPFC) at key postnatal stages. RNA sequencing at postnatal day 1 (P1) revealed significant transcriptional changes, particularly in genes associated with neuronal migration and differentiation, with a diminished effect by P14. Histological analysis identified a transient imbalance in inhibitory neuron subpopulations, PNS decreased the density of early-born neurons derived from the medial ganglionic eminence (MGE) while increasing late-born neurons derived from the caudal ganglionic eminence (CGE) at P1. EdU labeling confirmed that these shifts were time- and subtype-specific, affecting inhibitory neuron proliferation at distinct embryonic stages. By P15, these neuroanatomical alterations largely resolved, yet behavioral abnormalities persisted into adulthood. Our findings suggest that PNS disrupts inhibitory neuron development during a critical early window, leading to lasting behavioral consequences despite the transient nature of anatomical changes. This study highlights the selective vulnerability of inhibitory neuron subtypes to early-life stress and provides insight into potential mechanisms underlying stress-related psychiatric disorders.